Microbiological Analysis of Well Water Quality in Market and Residential Areas of Kendari City - La Ode Muhammad Erif; Tuwu, Eka Rahmatiah; Yasin, Asramid; Wahyuni, Ira Ryski; Kete, Surya Cipta Ramadhan; Qadri, Muhammad Saleh; Muhsimin; Hidayat, Herlan; Teke, Junartin; Fahidu, Wa Ode Hastiani; Setiawan, Agus; Abigael Kabe; Wiwin Rahmawati Nurdin (Journal of Soilscape and Agriculture, 2024)
Water is an essential element for human life; without water, humans will experience a lack of fluid, the fluid in the human body is around 50-80. Water can fulfill daily needs through human activities such as washing clothes, water for drinking, bathing, and so on. Well, water is suitable for use if it meets water quality standards. This type of research uses descriptive research methods. This research is located in Baruga Market, Anduonohu Market, Lorong Salangga, and Kendari Permai Kendari City in December 2023. the samples used in this study amounted to 4 wells. The results obtained in this study are that all well water is polluted with E. coli, and Baruga Market well water exceeds the quality standards for Coliform parameters.  The presence of E. coli in all well water samples indicates fecal contamination, posing severe health risks such as waterborne diseases. Baruga Market's well water exceeds Coliform standards, likely due to sewage runoff, making it unsafe without treatment. Immediate actions, like improving sanitation and providing clean water alternatives, are necessary to prevent further contamination and protect public health.